2016
DOI: 10.1177/0013916516636423
|View full text |Cite
|
Sign up to set email alerts
|

Is Planting Equitable? An Examination of the Spatial Distribution of Nonprofit Urban Tree-Planting Programs by Canopy Cover, Income, Race, and Ethnicity

Abstract: This article examines the spatial distribution of tree-planting projects undertaken by four urban greening nonprofit organizations in the Midwest and Eastern United States. We use a unique data set of tree-planting locations, land use data, and socioeconomic information to predict whether a census block group (n = 3,771) was the location of a tree-planting project between 2009 and 2011. Regression results show tree-planting projects were significantly less likely to have occurred in block groups with higher tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 66 publications
(83 reference statements)
1
27
0
Order By: Relevance
“…Watkins et al (2016) found that nonprofit tree-planting programs were more likely to occur when the proportions of African American and Hispanic/Latinx residents were smaller in a neighborhood (although they found a negative relationship between planting and income) and another study found no relationship between tree requests and the percent of neighborhood residents who were White (Locke and Baine, 2015). If inequity is found to be higher on public land than on private land (see for example), it more directly implicates the behavior of public and nonprofit actors.…”
Section: Measurementmentioning
confidence: 99%
“…Watkins et al (2016) found that nonprofit tree-planting programs were more likely to occur when the proportions of African American and Hispanic/Latinx residents were smaller in a neighborhood (although they found a negative relationship between planting and income) and another study found no relationship between tree requests and the percent of neighborhood residents who were White (Locke and Baine, 2015). If inequity is found to be higher on public land than on private land (see for example), it more directly implicates the behavior of public and nonprofit actors.…”
Section: Measurementmentioning
confidence: 99%
“…Watkins et al (2016) found that nonprofit tree-planting programs were more likely to occur when the proportions of African American and Hispanic/Latinx residents were smaller in a neighborhood (although they found a negative relationship between planting and income) and another study found no relationship between tree requests and the percent of neighborhood residents who were White (Locke and Baine, 2015). If inequity is found to be higher on public land than on private land (see Pham et al, 2012 for example), it more directly implicates the behavior of public and nonprofit actors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their contributions to mitigating climate change (Nowak, 1993), new planted trees promise to provide local benefits to the communities in which they are planted. However, early evidence cautions that urban forestry programs have the potential to create or exacerbate inequity by planting in areas with higher existing canopy cover, higher income (Donovan and Mills, 2014; Locke and Grove, 2016), and with fewer minority residents (Watkins et al, 2016). Even were these programs to plant in low-income and minority neighborhoods, they might yield unintended consequences such as ecological gentrification—increasing property values and forcing low-income renters to relocate (Dooling, 2009; Pearsall and Anguelovski, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Aerial photograph (left image) and green cover distribution (from left to right: Waveform lidar from our analysis (1Á5 m resolution), national land cover (NLC25) at 25 m resolution and European land cover (EULC100) at 100 m resolution). sociology (Watkins et al 2017), and politics (Heynen 2006). By way of example, there has been a great deal of research into the relationships between human health/well-being and the distribution of urban vegetation based on greenspace estimates derived from remotely sensed data of similar spatial resolutions to the satellite-derived datasets compared in this study (see Table 1 in Supporting Information for references), including (i) broad grain size land cover maps capable of detecting objects larger than 2 ha; (ii) land cover maps with a spatial resolution of 100 m; (iii) land cover maps with a spatial resolution of between 25 and 30 m; (iv) optical remote sensing products with a spatial resolution between 20 and 30 m; (v) land cover maps with a 10 m spatial resolution; and (vi) town planning maps which are able to detect vegetation at sub-10 m spatial resolution, but which omit private gardens.…”
Section: Discussionmentioning
confidence: 99%